(untitled) (Journal of Innovation in Academia, 2025)
Ironizing the violence to convey the political message about minority, Saadat Hasan Monto uses humanistic radical irony as a vehicle for political commentary by demystifying the politics of the representation of violence in official texts of both modern India and Pakistan. In that course Manto also subverts the limited and biased notion of partition, which took partition of India as only the partition of territory and people. In the light of Hutcheon’s notion of ‘radical use of irony’, I argue that Manto’s use of irony in “Cold Meat” and “Open it” shows the utter cruelty of the people in power and authority at the time of partition violence and humanity shown by the marginalized section of society. The humanity that shines through in his writings about the down-trodden people living in the fringes of society, and the victims of partition violence of 1947 are an integral part of his stories.